Delicate Tuning of the Ni/Co Ratio in Bimetal Layered Double Hydroxides for Efficient N2 Electroreduction. Issue 6 (15th February 2022) - Zou, Zhi; Wu, Lei; Yang, Fangqi; Cao, Chenliang; Meng, Qiangguo; Luo, Junhui; Zhou, Weizhen; Tong, Zhikun; Chen, Jingwen; Chen, Shixia; Zhou, Shaodong; Wang, Jun; et al.
Abstract: Electroreduction of N2 to NH3 at ambient conditions using renewable electricity is promising, but developing efficient electrocatalysts is still challenging due to the inertness of N≡N bonds. Layer double hydroxides (LDHs) composed of first‐row transition metals with empty d‐orbitals are theoretically promising for N2 electroreduction (NRR) but rarely reported. Herein, hollow NiCo‐LDH nanocages with different Ni/Co ratios were prepared, and their electronic structures and atomic arrangements were critical. The synergetic mechanisms of Ni and Co ions were revealed, and the optimized catalytic sites were proposed. Besides, in‐situ Raman spectroscopy and 15 N2 isotopic labeling studies were applied to detect reaction intermediates and confirm the origin of NH3 . As a result, high NH3 yield of 52.8 μg h −1  mgcat −1 and faradaic efficiency of 11.5 % were obtained at −0.7 V, which are top‐ranking among Co/Ni‐based NRR electrocatalysts. This work elucidates the structure–activity relationship between LDHs and NRR and is instructive for rational design of LDH‐based electrocatalysts. Abstract : Chemical composition matters : Hollow Ni/Co layered double hydroxide (LDH) nanocages are applied as electrochemical N2 reduction (NRR) catalysts. The correlation between the chemical/electronic structures of LDHs and their NRR electrocatalytic activities is revealed. After balancing the activation of the active sites and the NRR/hydrogen evolution reactivities, Co−Ni−Ni sites are recognized as the optimized NRR active center.